THE IMPACT OF THE CORONA VIRUS ON GLOBAL ECONOMIES IN GENERAL AND THE IRAQI ECONOMY IN PARTICULAR - Rajaa Jaber Abbas, Hind Ghanim Mohammad Al-Mohana, Abdulhussein Jalil Abdulhasan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Since the emergence of the Covid-19 crisis in China, the global and Arab economies are witnessing a wave of economic turmoil that formed a shock, whether on the supply or demand side. Which led to a decline in all Arab and global economic activities as companies closed in many countries and closed workplaces and schools, as well as tourism. As for the countries that depend on the rentier side, the decline in crude oil prices and the decline in its production has a negative impact on the public budgets of these countries. Which have contributed to the exacerbation of living conditions in the countries that do not have a health system and high operational capabilities in terms of the increase in the number of unemployment, the increase in poverty and the trend health spending instead of consumer spending. Which is due to bad management in the politics of these countries.